Spr Based Biosensors Design for Detection of Different Skin Types Cancer - V.L, Nandhini; K. Suresh Babu, Dr.; Manna, Moumita (International Journal of Engineering and Technology, 2018)
The progress in the field of bio-medical is increasing rapidly. SPR based melanoma provides the accuracy to detect the affected cancerous cell on any skin types. The growth in the small black spot in malignant and invasive melanoma of normal cell over affected cell is unpredictable to detect cancer in any skin types biosensing application sensors have by focusing on the graphene layer. The FDTD simulation guides the SPR to provide the configuration concentration on the Metal-Insulator-Metal (MIM) layer. Simulations are performed on different types of Asian, Caucasian and Dark skin on SPR based biosensor. The ultra-high sensitivity of biosensors can be calculated at a higher rate using R-soft tool and the readings are observed in optical meter. From the obtained simulation results, the sensitivity of the Asian skin is 8812nn/RIU, Caucasian skin is found to be 6064nm/RIU and Dark skin is 9290nm/RIU. The design is emphasized in a way that will show various application on melanoma detection with a sensitivity of 8055nm/RIU for the wavelength of 1550nm. It has been observed that for 1550 nm wavelength.The light speed at which the waveguide travels is up to 3*10-8 m/s. Finally, the sensitivity, accuracy and quality factor has been computed and found to be very high.Â Â Â